Contractual Freedom and its Limits in Modern Civil Law Governance - Pelupessy, Berd Elkiopas (Jurnal Hukum dan Keadilan, 2026)
The principle of freedom of contract is one of the main pillars of Indonesian civil law that guarantees the private autonomy of the parties in forming and determining the content of the agreement. However, in modern civil law practice, this principle is no longer understood as absolute, but rather experiences limitations to achieve justice and balance in contractual relationships. This study aims to analyze the position of the principle of freedom of contract in the Indonesian civil law system, while also examining the form and implications of its limitations through the principles of good faith, propriety, balance of the parties, as well as state intervention and the role of judges. The research method used is normative legal research with a statutory, conceptual, and doctrinal approach, which is based on an analysis of the provisions of the Civil Code, especially Articles 1320, 1337, 1338, and 1339, and supported by the opinions of scholars and the development of modern civil law doctrine. The results of the study indicate that the principle of freedom of contract remains relevant as a foundation for legal certainty and economic dynamics, but its application is limited to protect the weaker party and prevent abuse of bargaining position. These restrictions actually strengthen substantive justice without eliminating legal certainty, by shifting the paradigm of freedom of contract from formal freedom to freedom that is just and responsible.